Outcome quality in participant sport and recreation service quality models: Empirical results from public aquatic centres in Australia. Issue 5 (November 2016) - Howat, Gary; Assaker, Guy
Highlights: The present study assumes a hierarchical, multidimensional scheme for process quality and outcome quality. Using partial least squares structural equation modelling (PLS-SEM). Overall satisfaction fully mediates the impact of value, outcome quality and process quality on loyalty. Abstract: The role of service quality outcomes has often been understated in service quality models for participant sport and recreation. The aims of this study were to validate a range of outcome quality dimensions and to compare the relative influence on loyalty of outcome quality compared to process quality and value. Using data from 2109 customers of eight public aquatic centres in Australia the results validated four first-order outcome quality dimensions which in turn determined a higher-order outcome quality construct. Moreover, the results demonstrated that a process quality construct had the most significant impact on loyalty mediated by overall satisfaction, followed by outcome quality and value. These results provide both theoretical and practical insights in terms of managing service quality in the context of community sport and recreation in general and public aquatic centres in Australia, in particular.